New and poorly known Meligethes Stephens from China, with bionomical data on some species (Coleoptera: Nitidulidae: Meligethinae) - Liu, Meike; Huang, Min; Cline, Andrew Richard; Audisio, Paolo (Zootaxa, 2018)
Meligethes (Odonthogethes) trapezithorax sp. n., M. (O.) tricuspidatus sp. n., and M. (O.) luteomaculatus sp. n. are described from Hubei Province, China, based on a series of recently collected specimens. The new species appear morphologically closely related to M. (O.) brassicogethoides Audisio, Sabatelli & Jelínek, 2015 from Yunnan [M. (O.) trapezithorax sp. n.], M. (O.) occultus Audisio, Sabatelli & Jelínek, 2015 from Yunnan [M. (O.) tricuspidatus sp. n.], as well as M. (O.) pallidoelytrorum Chen & Kirejtshuk, 2013 from Sichuan and M. (O.) simulator Audisio, Sabatelli & Jelínek, 2015 from Shaanxi and Gansu [M. (O.) luteomaculatus sp. n.]. The new species clearly differ from their closely related taxa by details of body shape and color, and the distinct shape of the male and/or female genitalia. The previously unknown male of the rare and localized M. (M.) elytralis Audisio, Sabatelli & Jelínek, 2015 from Sichuan is described for the first time, and new distributional data of other Chinese species of the genus are presented, including M. (M.) semenovi Kirejtshuk, 1979 from Hubei, M. (M.) macrofemoratus Liu, Yang, Huang, Jelínek & Audisio, 2016 from Hubei, M. (M.) auropilosus Liu,Yang, Huang, Jelínek & Audisio, 2016 from Hubei, M. (O.) flavicollis Reitter, 1873 from Chongqing, M. (O.) wagneri Rebmann, 1956 from Shaanxi, M. (O.) pectoralis Rebmann, 1956 from Guizhou, and M. (O.) pseudopectoralis Audisio, Sabatelli & Jelínek, 2015 from Sichuan. Meligethes (M.) cinereoargenteus is moved from the Meligethes nepalensis species group to the Meligethes auripilis species group. Additional data on geographic distribution and larval ecology of other species in the genus are also reported. An updated species checklist of the genus Meligethes is presented.